Low-energy-consumption preparation process for greatly improving working voltage of tantalum electrolytic capacitor

By optimizing the anodizing process of tantalum electrolytic capacitors, using electrochemical methods and specific electrolyte components, the working voltage and withstand voltage of tantalum electrolytic capacitors are improved, and the problems of low working voltage and large leakage current in the existing technology are solved, and the Highly efficient preparation of tantalum electrolytic capacitors.

CN119181597APending Publication Date: 2024-12-24XUZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411255470.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The working voltage of existing tantalum electrolytic capacitors is low, which cannot meet the application needs in the high voltage field, and the preparation process cannot effectively reduce leakage current, resulting in waste of energy.

Method used

By optimizing the anodic oxidation process, the polishing pretreatment of the tantalum anode was performed by electrochemical method, mixed acids of hydrofluoric acid and concentrated sulfuric acid were used, and ascorbic acid and nanosilicon dioxide were added during the anodic oxidation process to form a high-quality Ta2O5 dielectric film , increase the working voltage and withstand voltage of the tantalum electrolytic capacitor.

Benefits of technology

The operating voltage of the tantalum electrolytic capacitor is increased to 240V, which significantly reduces leakage current, saves energy consumption, improves dielectric performance, and broadens application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181597A_ABST
    Figure CN119181597A_ABST
Patent Text Reader

Abstract

The invention provides a low-energy-consumption preparation process for greatly improving the working voltage of a tantalum electrolytic capacitor, which comprises the following steps of: pre-treating a tantalum anode foil or an anode block before anodic oxidation, boiling and washing after pre-treatment, and then cleaning to remove residual fluorine ions; carrying out anodic oxidation on the cleaned tantalum anode; and finally, a solid conductive material is coated as a cathode to obtain the solid tantalum electrolytic capacitor. The tantalum oxide film with excellent dielectric property is obtained through the method. The maximum working voltage of the solid tantalum electrolytic capacitor prepared on the basis can reach 240V, which is far higher than that of the current commercial tantalum electrolytic capacitor. Besides, according to the preparation process of the tantalum electrolytic capacitor provided by the invention, 90V withstand voltage of the capacitor can be realized when the anodic oxidation voltage is 100V, while only 30-50V withstand voltage can be realized when the anodic oxidation voltage is 100V in the traditional preparation process, so that the energy consumption in the manufacturing of the tantalum electrolytic capacitor is greatly saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-energy consumption preparation process for improving the working voltage of a tantalum electrolytic capacitor, and belongs to the technical field of preparation of tantalum electrolytic capacitors of electronic components. Background Art

[0002] It is understood that tantalum electrolytic capacitors have been an indispensable electronic component in the fields of national defense, aerospace, rail transportation, medical electronics and consumer electronics since their introduction in the 1950s. The advantages of tantalum electrolytic capacitors are their high reliability, high volume capacitance density, wide operating temperature range and excellent high-frequency characteristics, but their biggest disadvantage is their low operating voltage.

[0003] So far, the maximum operating voltage of commercial tantalum electrolytic capacitors still cannot exceed 100V, which seriously restricts the application of tantalum electrolytic capacitors in high-voltage fields. In addition, in order to meet safety requirements, the operating voltage of tantalum electrolytic capacitors is often limited to no more than 1 / 3 or even 1 / 5 of its formation voltage. For example, a tantalum electrolytic capacitor prepared with a tantalum anode with a formation voltage of 100V can only work in a scenario not higher than 30V or even 20V, which is also a huge waste of energy. Therefore, the current preparation process of tantalum electrolytic capacitors, especially the anodizing process that determines the dielectric properties of the dielectric film, cannot meet the needs of high-voltage applications.

[0004] A search revealed that a Chinese patent with publication number CN101494120A discloses a cathode preparation process for a fully sealed non-solid electrolyte all-tantalum capacitor. This method involves surface treatment of the tantalum before sintering, and the surface treatment method uses one of nitric acid, sulfuric acid and hydrofluoric acid to remove metal impurities or organic pollutants on the surface; a Chinese patent with publication number CN103500658A provides a method for reducing the leakage current of a high-voltage, large-capacity tantalum electrolytic capacitor. This method involves cleaning the tantalum block with nitric acid before anodization to remove impurities. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a low-energy consumption preparation process that greatly improves the working voltage of tantalum electrolytic capacitors. By optimizing the anodizing process, the preparation of tantalum electrolytic capacitors with ultra-high working voltage (~240V) can be achieved, providing a new technology for the development of tantalum electrolytic capacitors with high working voltage and low leakage current.

[0006] The present invention provides a low-energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors, comprising the following steps: Step 1, anode preparation, the tantalum anode used is etched tantalum foil, flat tantalum foil or sintered porous tantalum block; Step 2, pretreatment, using an electrochemical method to perform polishing pretreatment on the tantalum anode, the acid used in the electrochemical method is a mixed acid consisting of a hydrofluoric acid solution and concentrated sulfuric acid; Step 3, boiling and washing, using boiling deionized water to boil and wash the pretreated tantalum anode; Step 4, rinsing, using deionized water to fully clean the boiled and washed tantalum anode; Step 5, anodizing, applying a constant current in an electrolyte at 70-95° C. to form an amorphous Ta2O5 dielectric film, wherein the electrolyte contains an oxygen absorber and an additive, wherein the oxygen absorber is ascorbic acid or ammonium hypophosphite, and the additive is nano-silicon dioxide suspended particles; Step 6, cathode coating: coating the anodic-oxidized tantalum anode with a solid cathode conductive material and dripping carbon slurry and silver slurry to form a chip of a solid tantalum electrolytic capacitor.

[0007] The tantalum foil used in the present invention mainly refers to a porous tantalum foil prepared by an etching process and capable of providing a large specific surface area, or it may be a flat tantalum foil. The etching process may be electrochemical etching, chemical etching or laser etching, or may be a combination of one or more of the above methods; the preparation method of the porous tantalum block is to sinter tantalum powder at high temperature.

[0008] The present invention not only performs surface treatment before sintering, but also pre-treats the anode after sintering. It is different from the traditional chemical treatment method using acid. The traditional pre-treatment is to remove metal impurities or organic pollutants on the surface. The pre-treatment of the present invention adopts an electrochemical method, and the electrolyte used is a mixed acid of hydrofluoric acid and concentrated sulfuric acid. Its purpose is not only to remove impurities, but also to remove the natural passivation film that cannot be dissolved in acid, and to achieve the polishing of tantalum foil or tantalum block. This method is not only easy to operate, but also can accurately control the thickness of the removed tantalum matrix, and minimize the waste of raw materials. The electrochemical pre-treatment of the present invention can be completed in as short as 30 seconds with the assistance of forced polarization, which greatly improves production efficiency and saves costs.

[0009] Among them, the underlying principle of precise control of the tantalum matrix is ​​Faraday's law: the mass of the substance that undergoes chemical changes at the electrode interface is proportional to the amount of electricity input, that is: M=KQ=Kit. In electrochemical polishing, the current output by the power supply is constant, and the polishing time is known, so the total amount of charge output can be calculated. Electrochemical polishing is essentially the process of Ta metal being oxidized to become pentavalent Ta. Each tantalum atom transfers 5 electrons, and it is possible to calculate how many tantalum atoms the power output of the power supply can correspond to, and thus the mass of the tantalum metal is obtained. In summary, the electrochemical method of the present invention can control the amount of charge input by regulating the current density per unit time, thereby controlling the mass of the tantalum substrate removed.

[0010] The present invention adds an oxygen absorber and nano silicon dioxide particles to the electrolyte used for anodization, wherein the oxygen absorber is used to remove oxygen bubbles in the anodized film, and the nano silicon dioxide is used to prevent the anodized film from flashing. Finally, the withstand voltage of the tantalum electrolytic capacitor of the present invention can reach 240V.

[0011] When the current density is high, oxygen will inevitably be precipitated on the tantalum anode during the anodizing process. These oxygen will remain in the oxide film to form oxygen bubbles, which will cause a large local electric field concentration, resulting in premature breakdown of the oxide film. Therefore, using an oxygen absorber to remove oxygen bubbles can greatly improve the quality of the tantalum oxide film. The flash in the anodizing process is the electrolyte discharge phenomenon caused by the increase in the local field strength of the oxide film under high voltage, which will cause dendritic electrical breakdown characteristics on the surface of the oxide film. Therefore, adding low-dielectric-constant SiO2 to the electrolyte can increase the local breakdown field strength of the oxide film. The above two problems can only be reduced in the manufacture of tantalum electrolytic capacitors by reducing the current density, increasing the resistivity of the electrolyte, reducing the anodizing temperature or reducing the anodizing voltage. It should be noted that although reducing the current density, increasing the resistivity of the electrolyte, and reducing the anodizing temperature have certain effects, they also reduce the anodizing efficiency, which is not conducive to production.

[0012] The technical solution further optimized as the present invention is as follows: Preferably, the mass percent concentration of the hydrofluoric acid solution is 38%, and the volume ratio of the hydrofluoric acid solution to concentrated sulfuric acid is 1:9.

[0013] In step 2, a tantalum anode foil is used and the current density applied by the electrochemical method is 1-20 mA / cm 2 The current duration is 30-600s; the current density applied by the electrochemical method is 10-100 mA / cm 2 , the current duration is 30-600s.

[0014] In step 3, the boiling and washing time is 1-30 minutes; in step 4, the cleaning time is 1-5 minutes, and the standard for cleaning completion is that the fluoride ion concentration in the deionized water is less than 1 ppm.

[0015] Preferably, the solute of the electrolyte is one or more of phosphoric acid, nitric acid and sulfuric acid, and the concentration thereof is 0.01wt.%-0.1wt.%; the solvent of the electrolyte is deionized water, ethylene glycol or a mixture of the two.

[0016] Preferably, the concentration of the ascorbic acid or ammonium hypophosphite is 0.5 mM-50 mM; the concentration of the nano-silicon dioxide suspended particles is 0.1-0.5 wt.%.

[0017] In step 5, a tantalum anode foil is used, and the current density applied for anodization is 0.1-1 mA / cm 2 ; Tantalum anode block, the current density applied for anodization is 3-30mA / g.

[0018] In step 5, the holding time after the anodization reaches the set voltage is 10-60 minutes.

[0019] In step 6, the solid cathode conductive material is MnO2, pure PEDOT polymer, PEDOT polymer doped with different anions (such as poly (3,4-ethylenedioxythiophene)) or polypyrrole (PPy).

[0020] The present invention also provides a tantalum electrolytic capacitor prepared by the method.

[0021] In the process of the present invention, the initial tantalum anode is a tantalum anode foil or a tantalum anode block sintered at high temperature; the tantalum anode foil or anode block is first pretreated before anodization, and the tantalum anode foil or anode block is boiled and washed after the pretreatment, and then fully washed after boiling and washing, the purpose is to remove residual fluoride ions; then the cleaned tantalum anode is anodized; finally, a solid conductive material is coated as a cathode to obtain a solid tantalum electrolytic capacitor. A tantalum oxide film with very good dielectric properties is obtained by the above method. The maximum operating voltage of the solid tantalum electrolytic capacitor prepared on this basis can reach 240V, which is much higher than the current commercial tantalum electrolytic capacitor. In addition, the preparation process of the tantalum electrolytic capacitor proposed by the present invention can achieve a withstand voltage of 90V for the capacitor when the anodization voltage is 100V, while the traditional preparation process can only achieve a withstand voltage of 30-50V at an anodization voltage of 100V, so the present invention also greatly saves energy consumption in the manufacture of tantalum electrolytic capacitors.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention improves the preparation process of existing tantalum electrolytic capacitors to obtain a tantalum oxide film with better dielectric properties. The maximum operating voltage of the solid tantalum electrolytic capacitor prepared in this way can reach 240 V, which is far higher than the 65 V operating voltage of mainstream commercial tantalum electrolytic capacitors, greatly broadening the original application scenarios of tantalum electrolytic capacitors.

[0023] (2) The present invention improves the existing preparation process of tantalum electrolytic capacitors. The tantalum oxide film with a formation voltage of 300V can realize the preparation of tantalum electrolytic capacitors with a working voltage of 240V; under lower formation voltage conditions, the working voltage of tantalum electrolytic capacitors can reach 90% of the formation voltage (for example: the tantalum anode formation voltage is 100V, and the working voltage of tantalum electrolytic capacitors can reach 90V). If the original formation process is followed, anodization must be performed at a voltage higher than 300V to achieve the preparation of 65V tantalum capacitors. Therefore, the present invention greatly reduces the energy consumption of tantalum electrolytic capacitors in the manufacturing process and saves costs.

[0024] (3) The electrochemical pretreatment method adopted in the present invention has the advantages of being simple and controllable, and is convenient for automated production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the surface of the tantalum oxide film prepared according to the process in Comparative Example 1.

[0026] Figure 2 This is a SEM image of the cross section of the tantalum oxide film prepared according to the process in Comparative Example 1.

[0027] Figure 3 This is a SEM image of the surface of the tantalum oxide film prepared according to the process in Example 8.

[0028] Figure 4 This is a SEM image of the cross section of the tantalum oxide film prepared according to the process in Example 8.

[0029] Figure 5 This is a SEM image of the cross section of the tantalum oxide film prepared according to the process in Example 10.

[0030] Figure 6 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection authority of the present invention is not limited to the following embodiments.

[0032] like Figure 6 As shown, a low-energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors includes the following steps: Step 1, first prepare a tantalum anode foil or a porous tantalum anode block. The tantalum foil mainly refers to a porous tantalum foil prepared by an etching process to provide a large specific surface area, or it can be a flat tantalum foil. The porous tantalum block is prepared by high-temperature sintering. The etching process can be electrochemical etching, chemical etching or laser etching, or a combination of one or more of the above methods.

[0033] Step 2, pretreatment: Use electrochemical method to polish the tantalum anode for pretreatment, the purpose is to remove the surface passivation film. The pretreatment method is electrochemical method, the purpose is to remove the passivation film on the surface of the tantalum anode. The electrochemical method refers to electrochemical polishing the tantalum anode in a mixed acid of 38wt.% hydrofluoric acid + 98wt.% concentrated sulfuric acid (the volume ratio of hydrofluoric acid and concentrated sulfuric acid is 1:9) with the tantalum anode as the positive electrode; if the tantalum anode is tantalum foil, apply 1-20 mA / cm 2 The current density is 10-100 mA / cm2, and the current duration is 30-600s. If the tantalum anode is a tantalum block, 10-100 mA / cm2 is applied. 2 The current density is 10 mA / cm 2 , duration 180s.

[0034] Step 3, boiling and washing: boiling and washing the pretreated tantalum anode with boiling deionized water. The purpose of boiling and washing is to fully remove the fluoride ions adsorbed on the surface of the anode. The temperature of the deionized water is 100°C, and the duration is 1-30 minutes; more preferably, boiling and washing in 100°C deionized water for 20 minutes.

[0035] Step 4, rinsing: Use deionized water to fully rinse the tantalum anode after boiling and washing. The purpose of rinsing is to further remove the fluoride ions on the surface of the tantalum anode. The rinsing time is 1-5 minutes, and more preferably 3 minutes.

[0036] Step 5, anodization: apply a constant current in an electrolyte at 70-95°C to form an amorphous Ta2O5 dielectric film. The solute of the electrolyte is phosphoric acid with a concentration of 0.01 wt.%~0.1 wt.%; the oxygen absorber is 0.5mM~50mM ascorbic acid or ammonium hypophosphite; the additive is nano-SiO2 with a concentration of 0.01 wt.%~0.1 wt.%; the electrolyte solvent is deionized water, ethylene glycol, or a mixture of the two. The electrolyte is a 0.01wt.% phosphoric acid aqueous solution with 0.5mM ascorbic acid or ammonium hypophosphite and 0.1 wt.% nano-SiO2 added, and the solvent is deionized water.

[0037] Nano-SiO2 was purchased from Japan Carite Co., Ltd., and the particle size was less than 100 nm. If the particle size of nano-SiO2 is too large, it will not only fill the gaps in the etched foil or sintered block, resulting in loss of capacity, but also further reduce the breakdown field strength.

[0038] For tantalum anode foil, the applied current density is 0.1-1 mA / cm 2 The current density for tantalum anode block is 3-30mA / g. The current density for tantalum anode foil is 0.5mA / cm 2, the current density of the tantalum anode block is 10mA / g. As the anodizing process proceeds, the Ta2O5 oxide film on the tantalum anode will gradually become thicker, and the voltage applied to the tantalum anode will gradually reach the set voltage. The holding time after the anodizing reaches the set voltage is 10-60min. The holding time after the anodizing reaches the set voltage is 30min.

[0039] Step 6, cathode coating: coating the tantalum anode after anodization with a solid cathode conductive material and dripping carbon slurry and silver slurry to form a chip of a solid tantalum electrolytic capacitor. The solid cathode conductive material can be MnO2, pure or doped PEDOT (such as poly 3,4-ethylenedioxythiophene) polymer or PPy (polypyrrole) with different anions. The cathode conductive material is a complete film formed by drying after dipping in a PEDOT:PSS aqueous dispersion several times. PSS refers to polystyrene sulfonate. PEDOT:PSS dispersion was purchased from New Zhoubang Technology Co., Ltd., and the conductivity after film formation was about 30-50S / cm. Example 1

[0040] (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A dual-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in a mixed acid of hydrofluoric acid and concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9, and the hydrofluoric acid used was 38% hydrofluoric acid) and a current of 15 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 300 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 20 minutes, and then rinsed with room temperature deionized water for another 1 minute; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution, to which 0.5 mM ascorbic acid oxygen absorber and 0.01 wt.% nano-SiO2 were added, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 60min; (5) MnO2 is coated on the anodic-oxidized tantalum anode foil as a cathode, and carbon paste and silver paste are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 2

[0041] (1) Preparing a porous tantalum anode block obtained by a powder high temperature sintering method; (2) A dual-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode. The system was placed in a mixed acid of hydrofluoric acid and concentrated sulfuric acid (the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9, and 38% hydrofluoric acid was used) and a current of 10 mA / cm was applied.2 Electrochemical polishing was performed at a current density of 1000 nm for 60 s. (3) Place the pretreated tantalum anode block in boiling deionized water at 100°C for 5 minutes, and then rinse it with room temperature deionized water for another 2 minutes; (4) A double-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.05 wt.% phosphoric acid aqueous solution with 1 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.01 wt.%, and the current density was set to 30 mA / cm 2 , the holding time is set to 30min; (5) MnO2 is coated on the tantalum anode block after anodization as a cathode, and carbon slurry and silver slurry are drop-coated to form a chip of a solid tantalum electrolytic capacitor. Example 3

[0042] (1) Preparing a porous tantalum anode foil obtained by laser etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 15 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 30 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 10 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution with 2 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 60min; (5) PPy is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon paste and silver paste are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 4

[0043] (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 1 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 1000 μm for 600 s. (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 10 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A two-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution with 3 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 20min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 5

[0044] (1) Prepare a flat tantalum anode foil; (2) A two-electrode system was constructed with a flat tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 1 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 300 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 10 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A two-electrode system was constructed with a flat tantalum anode foil as the anode and a platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution with 0.5 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 20min; (5) MnO2 is coated on the tantalum anode block after anodization as a cathode, and carbon slurry and silver slurry are drop-coated to form a chip of a solid tantalum electrolytic capacitor. Example 6

[0045] (1) Preparing a porous tantalum anode block obtained by a powder sintering method; (2) A two-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 1 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 240 s; (3) Place the pretreated tantalum anode block in boiling deionized water at 100°C for 10 minutes, and then rinse it with room temperature deionized water for another 3 minutes; (4) A two-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution with 5 mM ammonium hypophosphite oxygen absorber added, the amount of nano-SiO2 added was 0.5 wt.%, and the current density was set to 3 mA / cm 2 , the holding time is set to 20min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 7

[0046] (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 10 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 1000 nm for 120 s. (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 5 minutes, and then rinsed with room temperature deionized water for another 2 minutes; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.1 wt.% phosphoric acid aqueous solution with 2 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 10min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 8

[0047] (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 10 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 180 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 20 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A two-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 0.5 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 30min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 9

[0048] (1) Preparing a porous tantalum anode block obtained by a powder sintering method; (2) A dual-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 10 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 1000 μm for 600 s. (3) Place the pretreated tantalum anode block in boiling deionized water at 100°C for 10 minutes, and then rinse it with room temperature deionized water for another 5 minutes; (4) A two-electrode system was constructed with a porous tantalum anode block as the anode and a platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 3 mM ammonium hypophosphite oxygen absorber added, the amount of nano-SiO2 added was 0.02 wt.%, and the current density was set to 10 mA / cm 2 , the holding time is set to 60min; (5) PPy is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon paste and silver paste are drop-coated to form a solid tantalum electrolytic capacitor chip. Example 10

[0049] (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 5 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 180 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 10 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 100 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 0.5 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.05 wt.%, and the current density was set to 30 mA / cm 2 , the holding time is set to 30min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip.

[0050] The performance test results of Examples 1-10 are shown in Table 1.

[0051] Table 1 Maximum operating voltage and leakage current of tantalum electrolytic capacitors prepared in various embodiments Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Working voltage / V 200 216 222 203 228 192 205 240 198 90 Leakage current / μA 2.80 3.13 1.80 2.07 2.80 5.37 3.88 1.12 2.69 1.15 Comparative Example 1 (Compared with Example 8) (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 0.5 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 30min; (3) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip.

[0052] Note that if anodization is performed directly without electrochemical polishing, the current density must be increased to 2 mA / cm 2 The above conditions can achieve the growth conditions of tantalum oxide film, which is higher than the current of Example 8 (0.1mA / cm 2 ) has increased by one order of magnitude, which seriously wastes energy; in addition, without the chemical polishing step, when the voltage is increased to 300V, it can be observed that the tantalum anode has a serious "flash fire" in the electrolyte, and the surface of the tantalum anode changes from bright to dark gray, which is a sign of crystallization of the tantalum oxide film, which leads to a serious reduction in the withstand voltage of the tantalum oxide film and a sharp increase in leakage current and loss.

[0053] Comparative Example 2 (Compared with Example 9) (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 10 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 1000 μm for 600 s. (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 5 minutes, and then rinsed with deionized water for another 3 minutes; (4) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 3 mM ammonium hypophosphite oxygen absorber added, and the current density was set to 10 mA / cm 2 , the holding time is set to 60min; (5) PPy is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon paste and silver paste are drop-coated to form a solid tantalum electrolytic capacitor chip.

[0054] The above experiments prove that even if the pretreatment process of electrochemical polishing is added, if there is a lack of nano-SiO2 particles as an additive in the electrolyte, local flashes may occasionally occur when the voltage is increased to 300V, causing the tantalum oxide film to break down.

[0055] Comparative Example 3 (Compared with Example 10) (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 5 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 180 s; (3) Rinse the pretreated tantalum anode with deionized water for 3 minutes; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 100 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution with 0.5 mM ascorbic acid oxygen absorber added, the amount of nano-SiO2 added was 0.05 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 30min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip.

[0056] If only rinsing is performed after pretreatment without boiling and washing, although no flash will occur when the voltage reaches 100V, it can be observed that crystallization has occurred in local areas of the oxide film. After performance testing of the tantalum electrolytic capacitor formed after coating the cathode, it was found that its maximum operating voltage was only 30V, far lower than the 90V with the addition of boiling and washing process. This is because there are still a large number of residual fluoride ions on the surface of the tantalum anode.

[0057] Comparative Example 4 (Compared with Example 8, the effect of oxygen absorbent) (1) Preparing a porous tantalum anode foil obtained by electrochemical etching; (2) A two-electrode system was constructed with a porous tantalum anode foil as the anode and a platinum metal sheet as the cathode. The system was placed in 38% hydrofluoric acid + concentrated sulfuric acid (where the volume ratio of hydrofluoric acid to concentrated sulfuric acid was 1:9) and 10 mA / cm was applied. 2 Electrochemical polishing was performed at a current density of 180 s; (3) The pretreated tantalum anode foil was placed in boiling deionized water at 100°C for 20 minutes, and then rinsed with deionized water at room temperature for another 3 minutes; (4) A double-electrode system was constructed with porous tantalum anode foil as the anode and platinum metal sheet as the cathode for anodic oxidation. The anodic oxidation voltage was set to 300 V, the electrolyte was a 0.01 wt.% phosphoric acid aqueous solution, the amount of nano-SiO2 added was 0.1 wt.%, and the current density was set to 0.1 mA / cm 2 , the holding time is set to 30min; (5) PEDOT:PSS is coated on the anodic-oxidized tantalum anode block as a cathode, and carbon slurry and silver slurry are drop-coated to form a solid tantalum electrolytic capacitor chip.

[0058] Table 2 Maximum operating voltage and leakage current of tantalum electrolytic capacitors prepared in various comparative examples Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Working voltage / V 55 60 30 79 Leakage current / μA 80.2 74 80.7 65 Figure 1-4 are tantalum oxide films grown according to the preparation processes described in Example 8 of the present invention and Comparative Example 1, respectively. Figure 1 and Figure 2 The SEM photos of the surface and cross section of the tantalum oxide film prepared according to the preparation process in Comparative Example 1 are shown in Figure 1. It can be seen from Figure 1 that there are a large number of crystallization defects distributed on the surface. The size of these defects can reach 5μm. From the cross-sectional view ( Figure 2 ) It can be found that there are a large number of hole defects in the tantalum oxide film. These defects are the main reasons for the low withstand voltage and large leakage current of tantalum electrolytic capacitors. Example 8 adds a pretreatment step based on the original anodizing process. Figure 3 It can be seen that the surface of the tantalum oxide film is very clean, with only a very small number of crystallization points. Figure 4It can be seen that there are no holes inside, so the dielectric properties of the tantalum oxide film are greatly improved. If the anodic oxidation voltage is further reduced (Example 10), Figure 5 It can be seen that there are no defects on the surface and inside of the tantalum oxide film, which is the fundamental reason why the working voltage of tantalum electrolytic capacitors can reach 90% of the anodic oxidation voltage. In short, the present invention proposes a very effective and feasible preparation process. The working voltage of the prepared tantalum electrolytic capacitor is nearly 4 times higher than that of the original process, and the leakage current is reduced by nearly 2 orders of magnitude, which greatly broadens the application scenarios of tantalum electrolytic capacitors.

[0059] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or substitutions within the technical scope disclosed by the present invention, which should be included in the scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A low-energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors, characterized in that: The following steps are involved: Step 1, anode preparation, the tantalum anode used is etched tantalum foil, flat tantalum foil or sintered porous tantalum block; Step 2, pretreatment, using an electrochemical method to perform polishing pretreatment on the tantalum anode, the acid used in the electrochemical method is a mixed acid consisting of a hydrofluoric acid solution and concentrated sulfuric acid; Step 3, boiling and washing, using boiling deionized water to boil and wash the pretreated tantalum anode; Step 4, rinsing, using deionized water to fully clean the boiled and washed tantalum anode; Step 5, anodizing, applying a constant current in an electrolyte at 70-95° C. to form an amorphous Ta2O5 dielectric film, wherein the electrolyte contains an oxygen absorber and an additive, wherein the oxygen absorber is ascorbic acid or ammonium hypophosphite, and the additive is nano-silicon dioxide suspended particles; Step 6, cathode coating: coating the anodic-oxidized tantalum anode with a solid cathode conductive material and dripping carbon slurry and silver slurry to form a chip of a solid tantalum electrolytic capacitor.

2. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1, characterized in that: The mass percent concentration of the hydrofluoric acid solution is 38%, and the volume ratio of the hydrofluoric acid solution to concentrated sulfuric acid is 1:

9.

3. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1, characterized in that: In step 2, a tantalum anode foil is used and the current density applied by the electrochemical method is 1-20 mA / cm 2 The current duration is 30-600s; the current density applied by the electrochemical method is 10-100 mA / cm 2 , the current duration is 30-600s.

4. According to claim 1, a low-energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors is characterized in that: In step 3, the boiling and washing time is 1-30 minutes; in step 4, the cleaning time is 1-5 minutes, and the standard for cleaning completion is that the fluoride ion concentration in the deionized water is less than 1 ppm.

5. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1, characterized in that: The solute of the electrolyte is one or more of phosphoric acid, nitric acid and sulfuric acid, and the concentration thereof is 0.01 wt.%-0.1 wt.%; the solvent of the electrolyte is deionized water, ethylene glycol or a mixture of the two.

6. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1 or 5, characterized in that: The concentration of the ascorbic acid or ammonium hypophosphite is 0.5 mM-50 mM; the concentration of the nano-silicon dioxide suspension particles is 0.1-0.5 wt.%.

7. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1 or 6, characterized in that: In step 5, a tantalum anode foil is used, and the current density applied for anodization is 0.1-1 mA / cm 2 ; Tantalum anode block, the current density applied for anodization is 3-30mA / g.

8. A low energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors according to claim 1 or 7, characterized in that: In step 5, the holding time after the anodization reaches the set voltage is 10-60 minutes.

9. According to claim 1, a low-energy consumption preparation process for significantly improving the working voltage of tantalum electrolytic capacitors is characterized in that: In step 6, the solid cathode conductive material is MnO2, pure PEDOT polymer, PEDOT polymer doped with different anions, or polypyrrole.

10. A tantalum electrolytic capacitor prepared by the method according to any one of claims 1 to 9.